2014
DOI: 10.1007/s10048-014-0433-x
|View full text |Cite
|
Sign up to set email alerts
|

Migraine genetics: current findings and future lines of research

Abstract: In the last two decades, migraine research has greatly advanced our current knowledge of the genetic contributions and the pathophysiology of this common and debilitating disorder. Nonetheless, this knowledge still needs to grow further and to translate into more effective treatments. To date, several genes involved in syndromic and monogenic forms of migraine have been identified, allowing the generation of animal models which have significantly contributed to current knowledge of the mechanisms underlying th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 200 publications
0
7
0
Order By: Relevance
“…Classical genetic approaches have revealed several clear forms of familial migraine, such as familial hemiplegic migraine, and mutations related to familial migraine have been identified in the CACNA1A, ATP1A2, SCN1A, and PRRT2 genes . The syndrome known as cerebral autosomal‐dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is another example of migraine‐like genetic Mendelian disorder . However, most common forms of migraine are less well understood at the genetic level and are probably a result of both multigenetic and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Classical genetic approaches have revealed several clear forms of familial migraine, such as familial hemiplegic migraine, and mutations related to familial migraine have been identified in the CACNA1A, ATP1A2, SCN1A, and PRRT2 genes . The syndrome known as cerebral autosomal‐dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is another example of migraine‐like genetic Mendelian disorder . However, most common forms of migraine are less well understood at the genetic level and are probably a result of both multigenetic and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…The recent advent of array‐based technologies and second‐generation DNA sequencing has provided novel powerful tools for genetic analysis. Whole‐exome sequencing and whole‐genome sequencing may now significantly hasten the discovery of rare pathogenic variants with high penetrance …”
Section: Discussionmentioning
confidence: 99%
“…Patients with migraine and Meniere's disease are prone to experience MS especially in female patients . Mutations in genes related to vasculopathy and cortical spreading depression are responsible for vestibular symptoms and MS hypersusceptibility in migraine patients .…”
Section: Pathogenesis and Pathophysiologymentioning
confidence: 99%
“…[199][200][201] Studies have identified a number of genetic variations associated with a higher risk of developing COPCs, most of which involve the regulation of the immune, neural and endocrine systems, specifically related to sensory/pain processing. [202][203][204][205][206][207][208][209][210][211][212][213][214][215][216][217] Likewise, research demonstrates a strong familial component to developing COPCs. [218][219][220][221][222][223][224] Twin studies have been particularly helpful in establishing that COPCs co-aggregate, are strongly genetic and are separable from anxiety and depression.…”
Section: Genetic and Environmental Factorsmentioning
confidence: 99%